2005
DOI: 10.1577/m04-081.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Abundance Estimates from Mark–Recapture and Removal Techniques for Rainbow Trout Captured by Electrofishing in Small Streams

Abstract: Estimation of fish abundance in streams using the removal model or the Lincoln-Peterson mark-recapture model is a common practice in fisheries. These models produce misleading results if their assumptions are violated. We evaluated the assumptions of these two models via electrofishing of rainbow trout Oncorhynchus mykiss in central Idaho streams. For one-, two-, three-, and four-pass sampling effort in closed sites, we evaluated the influences of fish size and habitat characteristics on sampling efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
187
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(206 citation statements)
references
References 25 publications
13
187
6
Order By: Relevance
“…Previous studies (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005) have demonstrated that electrofishing removals can produce biased estimates of abundance because CP is lower than what is actually measured, producing abundance estimates that are too low, and in our case, removal efficiency estimates that were probably too high. We have no way of knowing true CP in this study.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Previous studies (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005) have demonstrated that electrofishing removals can produce biased estimates of abundance because CP is lower than what is actually measured, producing abundance estimates that are too low, and in our case, removal efficiency estimates that were probably too high. We have no way of knowing true CP in this study.…”
mentioning
confidence: 50%
“…Although CP from multipass removals averaged 0.78, we realized that this was probably an overestimate (Riley and Fausch 1992;Peterson et al 2004b;Rosenberger and Dunham 2005), which would in turn cause underestimation of population abundance and overestimation of removal efficiency (especially for age-0 fish). Estimates of abundance should therefore be considered minimum estimates, and estimates of CP and removal efficiency should be considered maximum estimates.…”
Section: Methodsmentioning
confidence: 86%
“…We examined patterns of population density among these three classes of streams (for methods see Rosenberger and Dunham 2005;Dunham and others 2007), and found that density of age 1+ fish differed among the three classes of streams (Kruskal-Wallis Analysis of Variance, X 2 =5.96, df=2, p = 0.02). In streams without a recent history of wildfire densities of age 1+ fish were highest (0.22 fish/m 2 ), those in burned streams were intermediate (0.17 fish/m 2 ), and densities in reorganized streams were lowest (0.05 fish/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…One disadvantage of using fish as ecological indicators is that their population densities are more difficult to estimate accurately and their catchability depends on a number of factors including electrofishing equipment, the characteristics of the river reach [11][12][13], and species-specific features such as morphology or behavior [14,15]. The estimation of catchability and intercalibration of data are important to combine data from different fishing teams and to develop protocols for future work or monitoring [12].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of catchability and intercalibration of data are important to combine data from different fishing teams and to develop protocols for future work or monitoring [12]. Habitat quality is often assessed during fish sampling [16,17] and inconsistency of habitat assessment among researchers has been also reported by several researchers (e.g., [18][19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%